2019
DOI: 10.1016/j.ajoc.2019.100498
|View full text |Cite
|
Sign up to set email alerts
|

Successful medical management of Pythium insidiosum keratitis using a combination of minocycline, linezolid, and chloramphenicol

Abstract: Purpose To report successful medical management of Pythium insidiosum keratitis using an antibiotic combination of minocycline, linezolid, and chloramphenicol. Observations A 20-year-old Japanese man was referred for visual disturbance, hyperemia, and discharge from his right eye. Slit-lamp examination revealed a paracentral corneal hyphate ulcer. His visual acuity was 20/28. Smear examination of corneal scrapings revealed a filamentous fungus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 9 publications
0
25
0
Order By: Relevance
“…1 The authors concluded that there was still a knowledge gap regarding the best treatment because conventional antifungal agents are not effective against P. insidiosum. Newer treatments such as linezolid, azithromycin, and PIAI were reported to be successful in healing the infection in small case series 8,16 and in vitro susceptibility testing. 22 Currently, TPK remains the most effective treatment but has to be done as early as possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 The authors concluded that there was still a knowledge gap regarding the best treatment because conventional antifungal agents are not effective against P. insidiosum. Newer treatments such as linezolid, azithromycin, and PIAI were reported to be successful in healing the infection in small case series 8,16 and in vitro susceptibility testing. 22 Currently, TPK remains the most effective treatment but has to be done as early as possible.…”
Section: Discussionmentioning
confidence: 99%
“…14 Recently, some Pythium keratitis cases were successfully treated with antibiotics, such as minocycline, azithromycin, chloramphenicol, and linezolid. 1,15,16 There is no standard treatment regimen for Pythium keratitis to date, but most of the patients undergo early therapeutic penetrating keratoplasty (TPK). 11 Pythium antigen immunotherapy (PIAI) has also been studied, but its efficacy remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive and aggressive infiltration of P . insidiosum could result in corneal perforation, anterior chamber, limbal and scleral invasions, or endophthalmitis in a few days or weeks (Lekhanont et al, 2009;Lelievre et al, 2015;Rathi et al, 2018;Agarwal et al, 2019;Badenoch et al, 2001;He et al, 2016;Maeno et al, 2019;Ros Castellar et al, 2017;Thanathanee et al, 2013;Sharma et al, 2015;Agarwal et al, 2018).…”
Section: Ocular Pythiosismentioning
confidence: 99%
“…Potential risk factors for pythiosis include farming exposure, direct contact with a water resource (i.e., lake, river, lagoon, swamp, or even swimming pool), and a history of travel to endemic countries, such as Thailand (Krajaejun et al, 2006b;Lelievre et al, 2015;Hasika et al, 2019;Appavu, Prajna & Rajapandian, 2019). Inappropriate hygiene of contact lens can pose a risk (Lekhanont et al, 2009;Lelievre et al, 2015;Badenoch et al, 2001;Maeno et al, 2019;Bernheim et al, 2019;Tanhehco et al, 2011;Barequet, Lavinsky & Rosner, 2013;Neufeld et al, 2018;Raghavan et al, 2018), and exposure to dust or some foreign body in their eyes (Bagga et al, 2018;Hasika et al, 2019) predisposes individuals with no agricultural activity to this infection. The incidence of pythiosis follows a seasonal trend (Hasika et al, 2019;Thanathanee et al, 2013) with outbreaks of Pythium keratitis occurring during the rainy season in Thailand (Thanathanee et al, 2013) and around June to September during monsoon season in South India (Hasika et al, 2019).…”
Section: Environmental (Extrinsic) Factorsmentioning
confidence: 99%
See 1 more Smart Citation